Effects of long‐term low oxygen tension in human chondrosarcoma cells. Issue 2 (18th October 2017) - Piltti, Juha; Bygdell, Joakim; Qu, Chengjuan; Lammi, Mikko J.
Abstract: The cell‐based therapies could be potential methods to treat damaged cartilage tissues. Instead of native hyaline cartilage, the current therapies generate mainly weaker fibrocartilage‐type of repair tissue. A correct microenvironment influences the cellular phenotype, and together with external factors it can be used, for example, to aid the differentiation of mesenchymal stem cells to defined types of differentiated adult cells. In this study, we investigated the effect of long‐term exposure to 5% low oxygen atmosphere on human chondrosarcoma HCS‐2/8 cells. This atmosphere is close to normal oxygen tension of cartilage tissue. The proteome was analyzed with label‐free mass spectrometric method and further bioinformatic analysis. The qRT‐PCR method was used to gene expression analysis, and ELISA and dimethylmethylene blue assays for type II collagen and sulfated glycosaminoglycan measurements. The 5% oxygen atmosphere did not influence cell proliferation, but enhanced slightly ACAN and COL2A1 gene expression. Proteomic screening revealed a number of low oxygen‐induced protein level responses. Increased ones included NDUFA4L2, P4HA1, NDRG1, MIF, LDHA, PYGL, while TXNRD1, BAG2, TXN2, AQSTM1, TNFRSF1B, and EPHX1 decreased during the long‐term low oxygen atmosphere. Also a number of proteins previously not related to low oxygen tension changed during the treatment. Of those S100P, RPSS26, NDUFB11, CDV3, and TUBB8 had elevated levels, while ALCAM, HLA‐B, EIF1, and ACOT9 were lower in the samples cultured at low oxygen tension. In conclusion, low oxygen condition causes changes in the cellular amounts of several proteins. Abstract : Long‐term low oxygen tension increased a number of gene expressions, while elevated ACAN and COL2A1 expressions did not reveal changes at secretion levels during the 4‐week exposure period. Still, the low oxygen tension‐induced trend of the expression of ACAN and COL2A1 was consistent and, therefore, we suggest that 5% low oxygen condition could act as a supportive factor for the known chondrogenicity and/or extracellular matrix production enhancing factors, such as bone morphogenetic protein 4 or Rho‐kinase inhibitor Y‐27632.